Cardioprotective effect of Erythrina stricta leaves on isoproterenol-induced myocardial infarction in rat - Kuppusamy, Asokkumar; Varadharajan, Subhadradevi; Josey, Christy; John, Honey; Sherin, Daphne; Chirakkan, Divia; Athiyappan, Gokul (Bangladesh Journal of Pharmacology, 2010)
<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">The cardioprotective activity of <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">Erythrina stricta<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> leaves against isoproterenol-induced myocardial infarction was studied. Wistar <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">albino rats were pretreated with leaf extract (200 mg/kg) daily for 28 days. After treatment, isoproterenol (8.5 mg/kg body weight, orally) was injected to rats at an interval of 24 hours for two days to induce myocardial injury. Cardioprotection was investigated by estimating the activities of serum <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; color: black; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">aminotransferase<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">, lactate dehydrogenase and creatinine kinase. Anti-oxidant enzymes such as superoxide dismutase, catalase, glutathione peroxidase, reduced glutathione and thiobarbituric acid reactive substances were determined. The activities of serum marker enzymes were increased significantly (p<0.05) in isoproterenol-induced rats. <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">E. stricta<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> leaf extract showed a decrease in serum enzyme levels and increase of antioxidant status. The results were confirmed by histopathological evidences. The present study concludes that <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">E. stricta<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> leaf extract has a prophylactic value in myocardial infarction. <input id="gwProxy" type="hidden" /><!–Session data–><input id="jsProxy" onclick="jsCall();" type="hidden" />